The Influence of Product and Service Quality on Consumer Loyalty at Bone Star Wholesale Store in Sorong City - Akmal Ridwan; Munifa; Renni Mayasari; Kamaluddin; Widya Digor Mufti (Universitas Muhammadiyah Makassar, 2026)
Customer loyalty remains a critical determinant of sustainability in the traditional retail sector, particularly in emerging regions where modern retail competition is intensifying. However, limited empirical studies have examined the determinants of loyalty in small-scale grocery businesses in Eastern Indonesia. This study investigates the effect of product quality and service quality on consumer loyalty at Bone Star Wholesale Store in Sorong City. Grounded in Signal Theory, product and service quality are conceptualized as positive signals that influence consumer trust and repeat purchase behavior. A quantitative approach was employed using purposive sampling, involving 102 customers. Data were analyzed using multiple linear regression. The findings reveal that both product quality (β = 0.525; p < 0.001) and service quality (β = 0.370; p < 0.001) have positive and significant effects on consumer loyalty, both partially and simultaneously. The model explains 66.7% of the variance in customer loyalty (Adjusted R² = 0.667), indicating strong predictive power. The results highlight that the synergy between reliable products and responsive service strengthens long-term customer relationships. The study contributes to the limited literature on traditional retail loyalty in developing regions and provides practical implications for small grocery businesses seeking to enhance customer retention through quality-based competitive strategies.